Association between physical activity levels and mild cognitive impairment in Chinese older adults: a cross-sectional study from the China health and retirement longitudinal study - Zhang, Lei; Chen, Wei; Miao, Haijun; Zou, Ting; Xiang, Xuan; Wu, Ruikai; Zhou, Xiaohui (Frontiers in Public Health, 2025)
BackgroundResearch indicates that mild cognitive impairment (MCI) in older adults is linked to physical activity; however, the relationship between varying levels of physical activity (PAL) and the risk of MCI needs further exploration.ObjectiveThis study explores the association and dose–response relationship between different levels of physical activity and MCI in older adults.MethodsUsing data from the 2020 China Health and Retirement Longitudinal Study (CHARLS), this cross-sectional analysis included 5,373 older adults aged 60 and above. Binary logistic regression models and restricted cubic spline (RCS) methods were employed to examine the association and dose–response relationship between different PAL levels and the risk of MCI in the overall population and subgroups. Sensitivity analyses were conducted to validate the robustness of the results.ResultsIn the overall study population, compared to the lowest PAL quartile, participants in the second PAL quartile had a significantly reduced risk of MCI by 21.3% (p < 0.05). Given that the second PAL quartile had the lowest risk of MCI, a logistic regression model was constructed using the second quartile as the reference group. The results showed that, compared to the second PAL quartile, participants in the first and fourth PAL quartiles had significantly increased risks of MCI by 27.1% (p < 0.05) and 38.2% (p < 0.05), respectively. In subgroup analyses, compared to the second PAL quartile, female participants in the third and fourth PAL quartiles had significantly increased risks of MCI by 50.1% (p < 0.05) and 89.0% (p < 0.05), respectively; participants aged 60–74 in the first and fourth PAL quartiles had significantly increased risks of MCI by 29.4% (p < 0.05) and 42.2% (p < 0.05), respectively; and rural residents in the fourth PAL quartile had a significantly increased risk of MCI by 33.5% (p < 0.05). In the Chinese older adult population, a dose–response relationship was observed between physical activity and the risk of MCI. The RCS curve showed that as physical activity increased, the risk of MCI gradually decreased, reaching a beneficial point at 900 MET-min/week, with the lowest risk at approximately 1,600 MET-min/week. Beyond 1,600 MET-min/week, the risk of MCI began to rise, reaching a significant increase at 2,100 MET-min/week. Sensitivity analyses confirmed the robustness of the findings.ConclusionPhysical activity levels between 900 and 2,100 MET-min/week are associated with a reduced risk of MCI in the Chinese older adult population. Using physical activity to predict the risk of MCI in this population is feasible, and moderate physical activity may be an effective strategy for preventing and managing MCI.